The Influence of Immertion on Marshall Parameters and Residual Strength Index of Rubber Asphalt Mixture - Indriani, Andi Marini; Utomo, Gunaedy; Amirudin, Amirudin (CIVED, 2024)
The bad drainage system in the road pavement area also causes the road body to be submerged in water for quite a long time, causing the bond between the asphalt and aggregate to loosen, resulting in decreased service life. Developments in the field of road construction have now implemented many innovative ideas, one of which is namely the use of rubber asphalt with asphalt containing natural rubber which has 1.5 to 2 times the strength compared to conventional asphalt. In evaluating the performance of an asphalt mixture, especially the AC-WC Wear layer mixture, it can be analyzed using the Marshall test method by taking into account the conditions being tested, namely the test object being immersion in water or continuously flooded with water. The method used in this research is an experiment with treatment conditions for AC-WC rubber asphalt mixture specimens which are continuously immersion in water for 1 day, 2 days and 3 days. The research results showed that there was an increase in the VMA, VIM, and flow parameters, while the VFB, stability, and Residual Strength Index parameters decreased with increasing soaking time. Based on the research results, it can be concluded that although there is an influence on the performance of the asphalt mixture with the use of rubber asphalt, the decrease that occurs is not too large and is still within the required specifications.